THE RECEPTION OF THE CEFR IN JAPANESE LANGUAGE EDUCATION: IN RESPONSE TO THE DUAL LAUNCH OF THE CEFR-LEVEL LABELING IN THE JLPT AND THE REGISTERED JAPANESE LANGUAGE TEACHER SYSTEM - NOTO, Kuniyuki (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
Beginning in 2025, results of the Japanese-Language Proficiency Test (JLPT) will include a reference to CEFR levels. Similarly, the newly introduced national certification for Japanese language teachers in 2024 has been designed with considerable alignment with the principles of the CEFR. In Uzbekistan, a CEFR C1 level has become a graduation requirement for foreign language majors, reflecting how the influence of the CEFR now extends well beyond Europe. However, the implementation of the CEFR in Japanese language education has not always faithfully reflected its original pedagogical philosophy. One notable example is the misalignment between curricular input and expected learning outcomes in Japanese language programs at Uzbek universities. This paper examines the relationship between JLPT levels and CEFR levels through the lens of study hours, aiming to highlight issues in the current state of university-level Japanese education. While both JLPT and the JF Standard tend to equate advanced proficiency with the B2 level, the analysis reveals that it is difficult for students at universities in Uzbekistan to attain the C1 level solely within the allocated instructional hours. This outcome highlights an inherent limitation of CEFR when applied to languages such as Japanese, which differ significantly from European languages for which the CEFR was originally conceived. Current applications of the CEFR in Japanese education often focus disproportionately on the six-level framework, neglecting the broader pedagogical concepts underpinning it. Universities must therefore set graduation requirements that are both realistic and informed by the CEFR’s original principles, and revise their curricula and assessments accordingly.